Are the gains from pulmonary rehabilitation the same in idiopathic pulmonary fibrosis and other interstitial lung diseases? - Özmen, İpek and Yıldırım, Elif and Karakış, Meral and Öztürk, Murat and Aydın, Rüya and Şahal, Emre (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Introduction: In addition to dyspnoea and cough in interstitial lung diseases (ILD), the main symptom is decreased effort capacity. Pulmonary rehabilitation (PR)is recommended besides medical treatment approaches in chronic respiratory diseases. PR programs include approaches such as exercise training, patient and family training, nutritional assessment and support, psychosocial assessment and support. COPD patients more often directed to PR programs, besides that PR is also recommended for ILD. In this study, we aimed to evaluate the PR-related gains in patinets with IPF and non-IPF ILD. Methods: This retrospective study that we evaluated the PR data, demographic features of the patients with ILD who completed PR program between 2017 and 2020. PR was an 8-week (2days) outpatient PR program including aerobic and strengthening exercises. The 6-minute walking test (6MWT) results, quality of life scores that were recorded at the beginning and end of the PR program were evaluated.The patients were evaluated in two groups, patinets with IPF and non-IPF ILD. Results: A total of 56 patients (30 IPF, 26 non-IPF) with mean age 62±10 were included in the study. Among IPF patients 23 (77%) of them were receiving antifibrotic drugs. Non -IPF patients were: Unclassified ILD 9(16%), nonspecific interstitial pneumonia (NSIP) 8 (14%), sarcoidosis 3(%5), fibrotic hypersensitivity pneumonitis (fHP) 3 (5%), sjogren 2 (4%), scleroderma 1(2%). Both in IPF and non-IPF groups improvement in 6MWT, SGRQ total score after PR were statistically significantly improved (p= 0.001, p=0.002), (p= 0.001, p=0.018). Inspiratory muscle evaluation, MIP statistically increased after PR both in IPF and non-IPF patients (p= 0.015, p=0.028). There no significant differences in gains after PR program in walking capacity, quality of life, maximum inspiratory pressure between IPF and non-IPF patients. Conclusion: PR programs provide significant gains both in patints with IPF and non-IPF ILD. It is important that patients should be directed to PR programs in the early stages of ILD.